1985
DOI: 10.1002/jcp.1041230103
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the platelet‐derived growth factor induced replicative response

Abstract: Quiescent cultures of density arrested BALB/c-3T3 cells have been sensitized to the growth stimulatory action of the platelet-derived growth factor (PDGF). Sensitization was achieved by depriving the cultures of PDGF prior to growth stimulation and was noted after transfer of cultures from medium supplemented with 10% serum to medium containing either an equivalent concentration of platelet-poor plasma or a low concentration (0.5%) of serum. Sensitized cultures required less pure PDGF for growth stimulation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
1987
1987

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…4). As we have previously shown (Scher et al, 1985), BALB/c-3T3 cell cultures arrested in 10% or 0.5% plasma were more sensitive to both PDGF and plasma induced DNA synthesis than cultures arrested in 10% serum. However, unlike the BP3T3 cells, the BALBh3T3 cell cultures arrested in 10% serum synthesized DNA in response to these growth factors.…”
Section: Growth Of Bp3t3 Cells In Serum or Plasma-supporting
confidence: 60%
See 3 more Smart Citations
“…4). As we have previously shown (Scher et al, 1985), BALB/c-3T3 cell cultures arrested in 10% or 0.5% plasma were more sensitive to both PDGF and plasma induced DNA synthesis than cultures arrested in 10% serum. However, unlike the BP3T3 cells, the BALBh3T3 cell cultures arrested in 10% serum synthesized DNA in response to these growth factors.…”
Section: Growth Of Bp3t3 Cells In Serum or Plasma-supporting
confidence: 60%
“…We have recently shown that confluent BALBk-3T3 cultures become sensitized to the mitogenic action of PDGF by transferring the cultures to plasma supplemented medium (Scher et al, 1985). In these sensitized cultures a higher percentage of cells synthesize DNA upon subsequent PDGF treatment than in cultures maintained in 10% serum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings indicate that the absolute quantity rather than the concentration of PDGF is important for PDGF activity (Scher et al, 1985). Therefore, a higher concentration of PDGF was used in the biochemical (protein synthesis) experiments.…”
Section: Resultsmentioning
confidence: 99%